Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/09168451.2020.1715201
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Annona muricata-derived polysaccharides in neuronal HT22 cell damage induced by hydrogen peroxide

Abstract: Crude extracts and phytochemical compounds derived from Annona muricata leaves have been demonstrated to exert neuroprotective effects. However, the neuroprotective effects of Annona muricata leaves-derived polysaccharide extracts (ALPs) have not been investigated. ALP treatment was shown to induce concentration-dependent antioxidant activity in HT22 cells, and to increase cell viability in H2O2-treated HT22 cells. These effects were correlated with a decrease in major components of oxidation, including: Ca2+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…Similarly, there are studies on the content of alkaloids and vanoids with strong antioxidant effects [20,39]. In this study, we investigated the radioprotective effect of AME as an agent shown to have anticarcinogenic, anticonvulsant, antiin ammatory, antioxidant, radioprotective (against Gamma-ray) and neuroprotective properties [10,22,28]. There are only a few studies on the radioprotective effect of AM in the literature [10,17,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there are studies on the content of alkaloids and vanoids with strong antioxidant effects [20,39]. In this study, we investigated the radioprotective effect of AME as an agent shown to have anticarcinogenic, anticonvulsant, antiin ammatory, antioxidant, radioprotective (against Gamma-ray) and neuroprotective properties [10,22,28]. There are only a few studies on the radioprotective effect of AM in the literature [10,17,21].…”
Section: Discussionmentioning
confidence: 99%
“…The rst defense mechanism against these harmful effects due to oxidative stress is provided by SOD. SOD neutralizes ROS to the less harmful compound hydrogen peroxide (H 2 O 2 ) [22]. However, excessive cellular H 2 O 2 accumulation increases oxidative damage by causing the formation of reactive free hydroxyl (OH-) radical [34,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AM, which contains many flavonoids, alkaloids and acetogenins in its leaves, is also used to manage infections, diarrhoea, dermatitis, diabetes, fever and cardiovascular problems [18]. In support of this traditional use, various studies have shown the anticancer, antioxidant, antiviral, antihaemolytic, sedative and neuroprotective effects of AM [19,20]. Radiation-induced peripheral nerve damage (RIPND) is permanent since nerve cells do not have the regeneration ability [21,22].…”
Section: Marmara Medical Journalmentioning
confidence: 99%
“…Our studies have also shown that galactose (68.4%) is the major monosaccharide among the A. muricata leaf polysaccharides (ALPS), followed by glucose (24.37%), mannose (9.81%), and other sugars. ALPS exert protective effects against oxidative stress-induced cellular damage and radiation-induced skin injury ( 20 , 21 ). However, there is no evidence supporting the cytoprotective role of ALPS against chemotherapy-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%